Habitat preference of leopard cat (Prionailurus bengalensis Kerr. 1792) in the Cisokan Hydropower Development Area, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Shanida SS, Megantara EN, Husodo T, Mutaqin AZ, Kendarto DR, Wulandari I. 2023.Habitat preference of leopard cat (Prionailurus bengalensis Kerr. 1792) in the Cisokan Hydropower Development Area, West Java, Indonesia. Biodiversitas 24: 2284-2293. Leopard cat (Prionailurus bengalensisKerr. 1792) can occupy various habitats, including degraded and human-modified landscapes such as agricultural lands, plantations, and settlements. Nonetheless, there is little information about their responses to infrastructure development impacts the habitat preference of leopard cats. This study aims to reveal the habitat preferences of leopard cats in the Upper Cisokan Pumped Storage (UCPS) hydropower development area, Cianjur Regency and West Bandung Regency, West Java. Direct observation was conducted to collect habitat preference in terms of biotic, abiotic and anthropogenic parameters and analyzed using Vanderploeg and Scavia's Resource Selection Index (VSI). The results showed that in term of biotic factors, leopard cats preferred natural forests, shrubs, and rice fields; tree canopy area of ??51%-75%, tree DBH >20 cm, tree height 0-5 m and 11-15 m, and tree density of 0-20 trees. Leopard cats preferred 76%-100% shrubs canopy; ground-plant cover of 26%-75% with withered grass cover of 76%-100%. According to their abiotic factors, leopard cats preferred habitats with north and south, gentle, and lower slopes. The leopard cats also preferred habitat with wet soil. In term of anthropogenic factors, leopard cats preferred habitat close to water sources (